Human Existence According To Hindu Philosophy - I Ketut Subagiasta; Ni Wayan Gateri (IAHN-TP Palangka Raya, 2024)
Existence means something that exists. If something exists, then that something will also no longer exist. In other words, there is and there is not. From being to not being is change. Something that exists becomes nothing that is change. It is commonly said that change is eternal or eternal or nitya. From eternal or nitya to not eternal or anitya. So it is important to understand human existence from the perspective of Hindu philosophy.